Cultural Schema and Reading Comprehension: A Means to an End - Dimassi, AbdelFattah Othman (2006)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by AbdelFattah Othman Dimassi Entitled, "Cultural Schema and Reading Comprehension: A Means to an End," August 2006. Thesis Advisor is Dr. Rodney Tyson. Available are both Soft and Hard Copies of the Thesis.